2017
DOI: 10.1088/1757-899x/274/1/012135
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Design Method of Intelligent platform trolley

Abstract: Abstract. In this paper, a design method of detachable intelligent platform trolley is presented. The detachable intelligent platform trolley has three driving modes, and the rubber blanket and the cardan joint in the structure filter effectively the road surface turbulence and improve the safety of the driver. The design idea of the active wheel fixed structure and the driven steering wheel structure is emphatically introduced. At last, The results show that the right panel of intelligent platform trolley as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Study found that an intelligent platform trolley can be made to research things and analyze various loads by concentrating stress (static) at right panel, connectors, front and back ends of trolley [1]. Communication interaction and also obstacles can be avoided by using raspberry pi and also a robot for making a trolley.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Study found that an intelligent platform trolley can be made to research things and analyze various loads by concentrating stress (static) at right panel, connectors, front and back ends of trolley [1]. Communication interaction and also obstacles can be avoided by using raspberry pi and also a robot for making a trolley.…”
Section: Literature Reviewmentioning
confidence: 99%